The effects of COVID-19 on beef consumer preferences and beliefs in Colombia: A logit model approach - Ramírez, Óscar; Charry, Andrés; Díaz, Manuel Francisco; Enciso, Karen; Mejía, Daniela; Burkart, Stefan (Frontiers Media, 2021)
The COVID-19 pandemic has brought impacts on the food system in several ways, such as on the supply and demand of food or changes in consumer preferences. However, little is known yet about these effects but needs to be analyzed to define actions and policies for crisis mitigation and achieving food system resilience and food security. In this article, we estimate the effect of the COVID-19 lockdown on changes in food consumer preferences in Colombia, applying a logit model approach for seven attributes, namely animal welfare, environmental sustainability, information on the origin and manufacturing of food, food appearance, food price, fair payment to the producer, and food packaging. In addition, we provide an analysis of changes in beef consumption during the lockdown, since the beef industry is among Colombia's most important agricultural activities and is heavily affected by substitution effects. Our results show that consumer beliefs regarding these attributes remained mostly stable, but that income is a determining factor for the decision to consume certain types of food, such as beef, rather than for possible changes in beliefs. This means that income ends up being decisive for the consumption of food such as beef and that, for its part, it does not have a greater weight in the change of beliefs of the people surveyed. The results will help the food system actors in defining interventions for achieving food security and resilience.